Need of the hour? does breast milk bank reduces perinatal morbidity and mortality: a retrospective observational study - E., Narayanan; Sajjid, Mohd; Kumar, Arun (International Journal of Contemporary Pediatrics, 2020)
Background: Human milk bank plays an essential role by providing human milk to infants who would otherwise not be able to receive human milk. The aims and Objectives is to study the morbidity and mortality outcome profile of babies fed with PDHM (pasteurized donor human milk) comparing data between Pre Human Milk Breast bank (2015) and Post Human Milk Breast bank (2016, 2017 and 2018). Methods: Milk bank collect, screen, store, process, and distribute human milk. Retrospective observational study was done in Department of Neonatology, Institute of Obstetrics and Gynaecology and Women and Children Hospital, Chennai. Data obtained retrospectively comparing data Pre HMB (2015) and Post HMB (2016, 2017 and 2018). Results: In this study authors collected the data comparing Pre human milk bank (Pre HMB) and Post human milk bank (Post HMB). After starting human milk bank, around 1799 babies were benefitted and 14.45 lakh ml milk was collected from 16000 donor mothers in last 3 years. Bacterial contamination rate of PDHM has reduced to 4.39% (2018) compared to 7.73% (2016) with P Value 0.0042 (statistically significant). CONS and Staphylococcus aureus were the most common Organisms isolated. There was reduction in morbidity profile like sepsis rate, NEC/ Feed intolerance and ROP profile. Mortality profile also reduced to (7.73-9.31%). Duration of hospital and Duration to attain full feeds were improved all GA group babies. Conclusions: In this study, after starting human milk bank there was reduction in mortality, morbidity outcome, sepsis. Duration to attain full feeds and duration of hospital stay reduced. We concluded that establishment of breast milk bank will be more useful and beneficial for all GA group babies for better outcome.